2021
DOI: 10.1101/2021.11.14.468503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global landscape of replicative DNA polymerase usage in the human genome

Abstract: The division of labour among DNA polymerase underlies the accuracy and efficiency of replication. However, the roles of replicative polymerases have not been directly established in human cells. We developed polymerase usage sequence (Pu-seq) in HCT116 cells and mapped Polε and Polα usage genome wide. The polymerase usage profiles show Polε synthesises the leading strand and Polα contributes mainly to lagging strand synthesis. Combining the Polε and Polα profiles, we accurately predict the genome-wide pattern … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Given that the leading and lagging strands are synthesised by distinct cellular machinery 4,7,[27][28][29] , the observed consistency in the rate and spectrum of mutations generated by DEN lesions is unexpected. These results point to a shared mechanism of lesion bypass, strongly suggesting the same translesion polymerases are recruited by both the leading and lagging strands replication machineries.…”
Section: Leading and Lagging Strand Mutagenesis Is Symmetricalmentioning
confidence: 99%
“…Given that the leading and lagging strands are synthesised by distinct cellular machinery 4,7,[27][28][29] , the observed consistency in the rate and spectrum of mutations generated by DEN lesions is unexpected. These results point to a shared mechanism of lesion bypass, strongly suggesting the same translesion polymerases are recruited by both the leading and lagging strands replication machineries.…”
Section: Leading and Lagging Strand Mutagenesis Is Symmetricalmentioning
confidence: 99%
“…As per our previous data, the ChIP-Seq detected overall increases to the γ-H2AX signal detected following auxin (IAA) treatment in both repeats (example in Figure 4A). We first checked whether the position of γ-H2AX signal correlated with known DNA replication features: replication initiation sites and replication termination zones (both mapped in HCT116 cells by alternative techniques by 33 and 32 ) and common fragile sites (CFS) 42 . However, no correlation could be found in either of the repeats (Figure 4B and Supplementary Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…We then identified the closest replication origin, as assigned by Koyanagi et al . to the γ-H2AX peak 32 , determining also whether the replication fork will reach the TSS in a codirectional or head-to-head orientation with the RNA Pol II. We found that γ-H2AX peaks are close to their nearest origin, on average only 29 kb away (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations